Large scale fiber bridging in mode I intralaminar fracture. An embedded cell approach. (1st April 2016) - Canal, L.P.; Pappas, G.; Botsis, J.
Abstract: Fiber reinforced composites can develop large scale bridging upon mode I fracture. This toughening mechanism depends on the constituents and the geometry of the specimen, and is especially important in unidirectional laminates when fracture is parallel to the fibers. The mode I intralaminar fracture behavior of unidirectional carbon-epoxy laminates was investigated by means of a three-dimensional multiscale model based on an embedded-cell approach. A double cantilever beam specimen was represented by an anisotropic homogeneous solid, while the bridging bundles ahead of the crack tip were included as beam elements. The failure micro-mechanisms controlling the crack propagation (namely, decohesion and subsequent failure of the bridging bundles) were included in the behavior of the different constituents. Numerical simulations were able to predict the macroscopic response, as well as the development of bridging and the growth of the crack. These results demonstrated the ability of the virtual testing approach to study complex fracture processes in composite materials. Finally, the developed model was employed to study the thickness effect and ascertain the influence of the constituents' properties on the energy released during fracture.